Why are we here?. Issue 4 (December 2022) - Mawson, T. J.
Abstract: If one believes in God, what should one say is the answer to the question of why we are here? In this article, I hope to show that when we ask why we are here we ask several different questions at once and that Theism allows (indeed dictates) that these different questions have very different answers. Appreciating these differences can remove at least that perplexity generated when an answer which could well be plausible were it to be given in response to one question of God's purpose for us is mislocated and treated as if it were an answer to another.